2022
DOI: 10.1186/s43141-022-00408-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny, and expression profiling analysis of shattering genes in rapeseed and mustard plants

Abstract: Background Non-synchronized pods shattering in the Brassicaceae family bring upon huge yield losses around the world. The shattering process was validated to be controlled by eight genes in Arabidopsis, including SHP1, SHP2, FUL, IND, ALC, NAC, RPL, and PG. We performed genome-wide identification, characterization, and expression analysis of shattering genes in B.napus and B. juncea to gain understanding into this gene family and to explain their expression patterns in fresh and mature siliques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis. Notable examples are not limited to but include APX, NPR, DOF, shattering genes, SOD, and PEBP [68][69][70][71][72][73]. Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies of various gene families in Brassicaceae have consistently indicated their expansion compared with Arabidopsis. Notable examples are not limited to but include APX, NPR, DOF, shattering genes, SOD, and PEBP [68][69][70][71][72][73]. Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42].…”
Section: Discussionmentioning
confidence: 99%